Primary surgical repair of prostatic urethral rupture following multiple pelvic fracture in a dog - Albernaz, Vinicius Gonzalez Peres [UNESP]; Quitzan, Juliany Gomes [UNESP]; Conceição, Renato Tavares [UNESP]; Paiva, Bruna Ribeiro [UNESP]; De Almeida Fabris, Isabella [UNESP]; Da Rocha, Paula Barreto [UNESP] (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2017)
Abdominal urethral rupture commonly occurs in male dogs after traumatic pelvic fractures and can lead to uroperitoneum, causing peritonitis and azotemia. The primary complications of urethral damage include strictures, incontinence and innervation injury. Here, we describe a case report of prostatic urethral rupture, treated by primary suture repair, that yielded early healing and recovery in a ten-year-old, male, mixed-breed dog who visited our facility within 24 hours of being struck by a car. Positive contrast urethrocystography resulted in leakage of the contrast medium into the abdominal cavity in a point caudal to the urinary bladder. Additional radiography revealed multiple pelvic fractures. During surgery, we found a laceration of the right prostatic lobe causing urethral rupture. We performed a full thickness simple continue suture with 7-0 polyglactin 910 to reestablish urethral continuity. The prostate capsule was also sutured in a simple continue pattern. A previously placed indwelling urinary catheter was kept inside to divert urine flow. On the third postoperative day, the animal withdrew the urinary catheter and started to urinate by himself. The conservative treatment of pelvic fractures enabled complete return to function on the 55th day. One hundred and fifty days after the trauma, no evidence of urinary stricture or another clinical sign was observed. Urethral wounds can be treated surgically by primary suturing and urinary diversion. A short healing time was experienced, and the indwelling urinary catheter was removed three days after surgery since there was no more urine leakage and the animal began voiding normally.
Keywords: Canine; Laceration; Surgery; Trauma; Urethra